Effects of temperature and thermal cycles on the mechanical properties of expanded polystyrene foam. (March 2022) - Tahir, Muhammad Naeem; Hamed, Ehab
Understanding the effects of high temperature and thermal cycles on the mechanical properties of expanded polystyrene (EPS) foam is critical for its use in sandwich panels. This paper presents an experimental investigation of these effects in typical environmental conditions that exist in construction applications. A total of 117 small specimens were cut from metal-faced sandwich panels with EPS core and were exposed to different numbers of thermal cycles and/or sustained high temperatures. The specimens were then loaded under compression, tension, and four-point bending for evaluating the degradation of the mechanical properties of the foam. The thermal cycles reflect typical surface temperature during daily summer conditions, with a period of 24 h each and with a temperature varying between 24°C to 80°C. The results show that the modulus of elasticity of EPS foam in compression reduced by about 38% after exposure to thermal cycles for 45 days, whereas the tensile and shear moduli reduced by about 5.7% and 13.8%, respectively. Exposure to sustained high temperature after thermal cycles led to larger degradation of the elastic and shear moduli in the range of 38%–50%. These degradations can lead to early failures in applications that rely on the EPS foam as a structural component like in insulating sandwich panels.